Manajemen Risiko Likuiditas di BMT ABC Jawa Timur - Satria Agus Susilo; Dina Fitrisia Septiarini (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
The purpose of this research is to find out whether the liquidity risk management applied by BMT ABC Jawa Timur. The research method used is descriptive qualitative. Unit of analysis is liquidity risk management applied by BMT ABC Jawa Timur. Data processing techniques in this research based on Miles and Huberman.Research results can be concluded that BMT ABC Jawa Timur in performing riskidentification use historic approach and emerge a pattern of yearly cycles and mapping the cash flow. Liquidity risk categorized in third quadrant with low frequency occurs and give severe impact while the risk is come. Risk mitigation focused in preventive action in order to avoid liquidity risk and develop contingency plan. BMT ABC Jawa Timur performing monitoring and controlling of liquidity risk, are supported by technology and come along with held an appointment regularly with all employees discuss about financial condition inBMT.